Colorimetric Estimation of Ezetimibe and Simultaneous Spectrophotometric Estimation of Ezetimibe with Atorvastatin Calcium in Tablet Formulation - DESHMUKH, D.D.; BHATIA, N.M.; MORE, H.N.; BHATIA, M.S. (Asian Journal of Chemistry, 2010)
A simple, sensitive and rapid colorimetric method for estimation of ezetimibe and spectrophotometric method for simultaneous estimation of atorvastatin calcium and ezetimibe in tablet formulations have been developed. Colorimetric method for the estimation of ezetimibe was based on the formation of ion pair complex of drug with dye. The method was based on the formation of bluish-green coloured complex with patent blue-V and hydrochloric acid. The coloured complex showed absorbance maxima at 636nm and obeyed Beer's law in the concentration range of 20-50μg/mL. Multi-wavelength method was employed for simultaneous estimation of atorvastatin calcium and ezetimibe from tablet formulation. Multi-wavelength method was used to eliminate interference due to absorbance of ezetimibe at the sampling wavelength for atorvastatin calcium and absorbance of atorvastatin calcium at the sampling wavelength for ezetimibe. Atorvastatin calcium and ezetimibe showed absorbance maxima at 245 and 232nm, respectively. Both the drugs obeyed Beer's law in the concentration range of 2.5-20μg/mL. Results of analysis for both the methods were validated statistically and by recovery studies. Both the methods were found to be precise and accurate and can be adopted for routine analysis of drugs in formulation. Both the methods involve no extraction or separation process for the estimation of two drugs.